ANALISIS JAWABAN SISWA MENURUT TIPE KEPRIBADIAN DALAM MENYELESAIKAN SOAL CERITA MATERI BANGUN RUANG - Esteria Nomiana; Agung Hartoyo; Dede Suratman (Jurnal AlphaEuclidEdu, 2021)
This studyaims to describe the answer errors of students with extrovert-introvert personalities when solving story problems with material blocks and cubes based on the newman procedure. This type of research is a qualitative descriptif study. The subject in this study involved 29 junior high school students. The object of this research is the extrovert-introvert personality student’s answer errors in solving block and cube story problems based on the newman procedure. Data collection techniques used were distributing personality questionnaires and test questions on blocks and cubes, as well as direct communication (interview).The results of the personality questionnaire taken were 3 students with high extrovert personalitiesand 3 students with high introvert personalities Analysis framework to reveal errors using newman procedure While the analysis technique uses qualitative data analysis of miles and huberman. The results of the errors made by students in this study were reading errors (R), misunderdtsnding problems (C),transgormation errors (P), and final answer errors (E).This mistakes made by extrovert-introverted students were mostly transformation errors (T), processing skills errors (P), and final answer errors(E). Keywords: Errors Answer, Extrovert-Introvert Persobality, Procedure Newman